Pembentukan Karakter TERTATA (Trengginas, Tanggap dan Tanggon) pada Pemuda Karang Taruna Cimahi - Litra Amanda Metra; Amir Nuyman Setyadiredja (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
Youth in the digital era face various psychological and social challenges, including decreased mental resilience, low social sensitivity, and difficulties adapting to the demands of early adulthood. These conditions are also experienced by some members of the Youth Organization (Karang Taruna) of RW 03, Cibeber Village, Cimahi City, who require structured and contextual character development. This community service program aimed to strengthen the TERTATA character values (Trengginas, Tanggap, and Tanggon) among youth through an experiential learning approach based on outdoor activities. The program was conducted at Curug Tilu Leuwi Opat, West Bandung Regency, on November 6, 2025, involving ten youth participants. The intervention integrated psychoeducation, group simulations, and structured reflection. Evaluation was carried out using a pre-test and post-test design with a TERTATA character instrument that had demonstrated adequate validity and reliability. The results showed a significant increase in participants’ TERTATA character scores after the program. Participants demonstrated a more comprehensive understanding of Trengginas, Tanggap, and Tanggon, along with positive changes in attitudes, including increased activeness, social sensitivity, and resilience in facing challenges. This program has the potential to serve as a community-based model for youth character strengthening.